(untitled) (Journal of Orofacial Research, 2018)
Objective: The purpose of the study was to determine the efficacy of three different mouthwashes in patients undergoing fixed orthodontic treatment for prevention of white spot lesions Methods: The study was conducted on 30 patients undergoing fixed orthodontic treatment between the ages of 15-25years. Patients were divided into 3groups - Group 1 control group, Group 2 using freshclor for 30 sec twice daily and group 3 using HiOra mouth wash for 30sec twice daily. Samples from tooth surfaces were collected at 1st day, 30th day and 90th day interval and were incubated for 48 hours. Colonies were counted using digital colony counter. Results: Freshclor and HiOra mouthwashes showed the maximum potential for the control of pathogenic organisms, and prevention of gingivitis and bacterial plaque inhibition than patients those were not using mouthwash.